A pesquisa como princípio pedagógico no ensino de Sociologia: uma análise a partir dos livros selecionados no PNLD 2015 - Amurabi Oliveira; Marcelo Pinheiro Cigales (Ciências Sociais Unisinos)
The academic debate about the teaching of sociology has been continuously promoted, especially since 2008, when the subject returned to the school curriculum in the whole country. However, new elements have emerged and have led to new research topics. Among them is the production and circulation of textbooks, considering mainly the introduction of Sociology in the National Textbook Plan (NTP) since 2012. While in the first bidding two books were selected, in the second one for the year 2015 six were selected, which mirrors the increase in production and the improvement of these cultural artifacts. In this article we contextualize the Sociology textbook as well as its introduction in the NTP and then examine how research is present in the activities of selected Sociology textbooks for the 2015 NTP, considering that research is understood in this paper as a pedagogical principle for the teaching of Sociology in accordance with the National Curriculum Guidelines (2006), which is deeply relevant in view of the central role that textbooks play in the practice of Elementary Education teachers. For a better analysis of this issue, we classify the research proposals in two types: methodological and informative research. At the end we notice the persistence of the latter type, which has a more superficial character, although there is a broad recognition of the importance of considering research as a pedagogical principle as well as a qualitative increase of this issue in the approved textbooks, so that we can consider that this is a phenomenon that is in a process of consolidation.